2019
DOI: 10.5187/jast.2019.61.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green tea leaf, lotus leaf, and kimchi powders on quality characteristics of chicken liver sausages

Abstract: Liver sausage is flavorful and highly nutritious. However, liver has a relatively short shelf life due to acceleration of oxidation in the presence of endogenous enzymes and metals. Powders derived from natural sources, including plants or fruits, are applied to meat products for inhibiting oxidation without adverse effects on their quality. Hence, this study investigated the effects of natural powders derived from green tea leaf (GTL), lotus leaf (LL), and kimchi (KC) on the quality and change in lipid oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Hence, in this scenario, herbs and their extracts can have useful potential applications with regards to their growth-promoting and multiple health benefits. The green tea leaf powder was able to maintain the freshness of chicken liver sausages by effectively retarding lipid oxidation (Choe, Kim, & Kim, 2019). Body weight, average daily weight gain, average daily feed intake and feed conversion ratio remained unaltered following the addition of GTE (125, 250, 500, 1,000 and 2000 mg/kg) to the diet of broiler chickens.…”
Section: Poultry Industrymentioning
confidence: 98%
“…Hence, in this scenario, herbs and their extracts can have useful potential applications with regards to their growth-promoting and multiple health benefits. The green tea leaf powder was able to maintain the freshness of chicken liver sausages by effectively retarding lipid oxidation (Choe, Kim, & Kim, 2019). Body weight, average daily weight gain, average daily feed intake and feed conversion ratio remained unaltered following the addition of GTE (125, 250, 500, 1,000 and 2000 mg/kg) to the diet of broiler chickens.…”
Section: Poultry Industrymentioning
confidence: 98%
“…Various raw materials are used in the production of combined pates: pumpkins [5], soybeans [6], girasole [7], ground cedar nuts [8], leaves of green tea and lotus, kimchi powder [9]. It was established that partial replacement of the raw material of animal origin with a plant raw material makes it possible to reduce not only caloric content of the product but also content of cholesterol and saturated fatty acids [5][6][7][8][9]. However, production of functional meat products has its own features, since it is necessary to preserve biological activity of the food additive and qualitative indicators of the final product.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The classic formulation of liver pates includes offal, dairy products and plant raw materials. Pates can be prepared from a variety of products in various combinations [5][6][7][8][9][10][11][12][13][14][15]. Soft consistency of the pates is achieved through special methods of raw material processing and careful choice of ingredients.…”
Section: The Study Of Rheological Indicatorsmentioning
confidence: 99%
“…Collagen contains approximately 30% protein and is widely used for the preparation of meat products owing to its functionality, including its effects on texture, water-binding ability, adhesion, and cohesion (Gomez-Guillen et al, 2011). Previous studies have shown that collagen or collagen mixtures with other functional ingredients improve the water holding capacity (WHC) in cured ham, reduced fat sausage, and chicken nuggets (Choe and Kim, 2019; Kim et al, 2015; Schilling et al., 2003). For these reasons, commercial collagen mixtures from various sources, especially those derived from pork, are widely sold as food additives.…”
Section: Introductionmentioning
confidence: 99%